2009
DOI: 10.1007/s11695-009-9877-8
|View full text |Cite
|
Sign up to set email alerts
|

Intragastric Balloon Followed by Biliopancreatic Diversion in a Liver Transplant Recipient: A Case Report

Abstract: Liver transplantation is a life-saving procedure for end-stage liver disease. In liver transplant recipients, morbid obesity influences post-operative survival and graft function. In 1996, our patient underwent a successful liver transplantation because of a HCV-related liver failure (body mass index (BMI) 31). Follow-up showed a functional graft and the development of severe obesity up to a BMI of 61 in January 2006. In January 2007, he was submitted to intragastric balloon therapy for 6 months, reaching a BM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 20 publications
0
10
0
1
Order By: Relevance
“…Bariatric surgery performed between 6 months and 10 years after LT has been described in case reports (14)(15)(16)(17). All of these reported cases have had minimal complications and patient outcomes appear satisfactory but with limited follow-up detail.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bariatric surgery performed between 6 months and 10 years after LT has been described in case reports (14)(15)(16)(17). All of these reported cases have had minimal complications and patient outcomes appear satisfactory but with limited follow-up detail.…”
Section: Discussionmentioning
confidence: 99%
“…Bariatric surgery may be suitable for patients with early-stage liver disease (11), but it is not indicated for patients with decompensated liver disease (12). Posttransplant bariatric surgery may be an option though requires two separate major operations and may be associated with increased technical difficulty due to adhesions and complications related to long-term immunosuppression (13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…These findings are comparable to %EWL seen in the nontransplant population that range from 53.3% in LSG and 62.6% in RYGB . In the post‐LT population, %EWL ranges from 43% to 76% in studies with a minimum of 12‐month follow‐up . In a recent series of 12 patients who underwent LSG following LT, Tsamalaidze et al demonstrated a change in BMI similar to a matched non‐LT cohort and a %EWL of 50% at 1 year .…”
Section: Discussionmentioning
confidence: 52%
“…Managing weight gain after transplantation is equally fraught with difficulties. Case reports of bariatric surgery performed 6 months to 10 years after LT exist 11‐14. All these reported cases have had minimal complications, and the patient outcomes were good during the limited follow‐up reported.…”
Section: Obesitymentioning
confidence: 99%